D'Ailly's "Epistola Diaboli Leviathan" - Raymond, Irving Woodworth (Church history, 1953)
The morning of April 8, 1348, began on an ominous note. Milling and shouting thousands covered the area of St. Peter's and surrounded the palace where the cardinals had entered into conclave the day before to elect the successor of Gregory XI, who had chanced to die before returning to Avignon. The Romans were desperate. For nearly seventy years they had lost to Avignon the revenues that had handsomely supported Rome. The city was poverty-stricken; churches and monasteries were in ruins, papal properties dissipated, and rebellion was smoldering. During the customary nine days elapsing between the death of the former pope and election of a new one, citizens and municipal officials of Rome had visited individual cardinals to inform them that they must elect a pope who would reestablish the Holy See in Rome, making it clear that they could not answer for the safety of the cardinals if the latter acted contrary to their wishes.